Community structure of the macrobenthos of the Iloilo River - a tidal inlet of the Iloilo Straight - Palla, Rocille Quilantang (2010.)
The study was conducted to determine the community structure of the macrobenthic fauna in Iloilo River. Samples were taken quarterly from 13 stations in March, 2007 and 15 stations in June, September and November, 2007., 43 taxa were ientified, dominated by polychaete worm, namely the Capitellidae and Sponidae. Overall annual mean density was 36268.83 indom2. Highest density was sampled on September, 2007 while lowest on march, 2007. Noticeable gradients an localized patterns were observed for abiotic and sediment characteristics, their complex interactions perhaps a major controlling influence on benthic distribution. The river can be divided into recognizable station groups namely: the seaward cluster charcterized by consistently high salinity, temperature depth, organic matter and silt-day composition; the inner station group which has the shallowest stations and lowest salinity; and the central station group which has the least organic matter content and high sand composition. Species assemblages were also identifiable for each station group, exhibiting high fidelity. Indications of a disturbed environment were also seen from the results of this study.
Thesis (Graduate, Master of Science in Biology) -- Miagao, Iloilo : College of Arts and Sciences, University of the Philippines of the Philippines Visayas, march 2010.
Keywords: Iloilo River -- Macrobenthos